A giant post auricular cutaneous horn: A rare case report - Joshi, Arpit Deepakkumar; Agarwal, Sanjeev; Joshi, Dhwanil (Indian Journal of Case Reports, 2019)
A cutaneous (cornu cutaneum) horn is a rare lesion which usually appears in sun-exposed areas and is very uncommon. It is a conical projection of hyperkeratotic epidermis and can be from a few millimeters to several centimeters in length. Here, we present the case of a large “horn” of long duration, arising in the right postauricular region in a 32-years-old male. The lesion was carefully examined, evaluated, complete excision was done with adequate margins and the defect was closed with primary closure after mobilizing the skin flaps adequately. Histopathologic examination showed the skin with underlying epidermis and extensive hyperkeratosis with no malignant cells seen at the base of the horn. It is important to mention that horn itself, is not the most important issue, but rather the underlying condition, which may be malignant also, needs to be ruled out and addressed.